Bionanocomposite Coating Film Technologies for Disease Management in Fruits and Vegetables - Jonathan M. Sánchez-Silva; Ulises M. López-García; Porfirio Gutierrez-Martinez; Ana Yareli Flores-Ramírez; Surelys Ramos-Bell; Cristina Moreno-Hernández; Tomás Rivas-García; Ramsés Ramón González-Estrada (Horticulturae)
Fruit and vegetable production is often impacted by microbial pathogens that compromise the quality of produce and lead to significant economic losses at the postharvest stages. Due to their efficacy, agrochemicals are widely applied in disease management; nevertheless, this practice has led to the appearance of microbial strains resistant to these types of agrochemicals. Additionally, there is growing concern among consumers about the presence of these chemical residues in fruits and the negative impacts they cause on multiple ecosystems. In response, there is a growing need for safe, effective, green, and sustainable disease control technologies. Bionanocomposites, with their unique ability to combine nanomaterials and biopolymers that have attractive properties, represents a promising alternative for postharvest disease control. These technologies allow for the development of functional coatings and films with antimicrobial, antioxidant, and barrier properties, which are critical for extending shelf life and preserving fruit quality. Recent advances have demonstrated that integrating nanoparticles, such as ZnO, TiO2, Ag, and chitosan-based nanosystems, into biopolymeric matrices, like alginate, pectin, starch, or cellulose, can enhance mechanical strength, regulate gas exchange, and control the release of active agents. This review presents systematized information that is focused on the creation of coatings and films based on bionanocomposites for the management of disease in fruits and vegetables. It also discusses the use of diverse biopolymers and nanomaterials and their impact on the quality and shelf life of fruits and vegetables.